Pengaruh Social Media Marketing dan Personal Branding Terhadap Keputusan Pembelian pada Produk Make Over di Mitufaya Kota Malang - Fauziyyah, Hani; Maskan, Mohammad; Kurniawan Murtiyanto, Rizki (Teewan Journal Solutions, 2025)
Currently, digital marketing is regarded as more effective and practical. Technological and communication advancements are rapidly evolving in line with increasing human needs. In addition to social media marketing, companies must also consider personal branding. Make Over was founded to provide high-quality and diverse cosmetic products for women. The growing number of cosmetic users in Indonesia presents an opportunity for business players such as cosmetic shops. One such shop is Mitufaya Malang, which offers a variety of cosmetics to meet consumer needs, particularly for women. This research aims to determine the influence of social media marketing and personal branding on purchase decisions for Make Over products at Mitufaya Malang This study was quantitative research with variables including social media marketing, personal branding, and purchase decisions. The purposive sampling technique was utilized for data collection through questionnaires, involving 100 respondents. The data analysis method employed was multiple linear regression analysis, which included classical assumption tests, hypothesis testing, and determination coefficient analysis. The results of the hypothesis testing, both partially and simultaneously, indicated that social media marketing and personal branding had a positive and significant influence on purchase decisions for Make Over products at the Mitufaya Malang cosmetic store. Based on the research findings, it can be concluded that social media marketing and personal branding are significant factors in making purchase decisions. Positive and effective social media marketing will enhance purchase decisions, while personal branding will attract customers to make purchase decisions.